(untitled) (Historia, 2022)
Zach de Beer’s political career began in 1950 when as a student leader and a membervof the Civil Rights League he addressed a public meeting in the Cape Town City Hall to protest the banning of the Communist Party. Forty years later, in February 1990, he was in parliament when President F.W. de Klerk announced the unbanning of the Communist Party, the African National Congress, and the Pan Africanist Congress. During the darkest years of the apartheid state he, along with others, kept liberal democratic ideals alive. In 1959 he helped to form the liberal Progressive Party, and in 1960 he opposed the banning of the African National Congress and the Pan Africanist Congress. This was a courageous action that would cost him his parliamentary seat in the 1961 general election and led to years in the political wilderness. Outside of parliament, as a prominent figure in the financial world, he continued to encourage constitutional and political reform. In 1988, he became leader of the Progressive Federal Party and played a leading role in the founding of the Democratic Party in 1989. This article shows that the party’s good performance in the general election of that year was a crucial factor in pushing De Klerk to initiate the dismantling of the apartheid state in 1990. In recognition of his contribution to the anti-apartheid struggle, President Nelson Mandela appointed him as South Africa’s ambassador to the Netherlands in 1994. Opsomming Zach de Beer se politieke loopbaan het in 1950 begin toe hy as ’n studenteleier en as ’n lid van die Civil Rights League ’n protesvergadering teen die verbanning van die Kommunistiese Party in die stadsaal van Kaapstad toegespreek het. Veertig jaar later in Februarie 1990 was hy in die parlement toe president F.W. de Klerk die Kommunistiese Party, die African National Congres en die Pan Africanist Congress wettig verklaar het. Gedurende die donkerste dae van die apartheidstaat het hy saam met ander liberale die ideal van ’n liberale-demokratiese bestel lewendig gehou. In 1959 het hy gehelp om die liberale Progressiewe Party te stig, en in 1960 het hy die onwettig verklaring van die African National Congress en die Pan Africanist Congress teengestaan. Dit was ’n dapper daad wat hom sy parlementêre setel in die algemene verkiesing van 1961 gekos het, en jare in die politieke wildernis tot gevolg gehad het. Buite die parlement het hy as ’n leidende figuur in die sakewêreld deurentyd op grondwetlike en politieke hervorminge aangedring. In 1988 het hy die leier van die Progressiewe Federale Party geword, en die volgende jaar ’n leidende rol gespeel in die stigting van die Demokraties Party. Hierdie artikel toon dat die Demokratiese Party se goeie vertoning in die algemene verkiesing van 1989 ’n belangrike faktor was om De Klerk te oortuig om met die aftakeling van apartheidstaat in 1990 te begin. In waardering van sy bydrae in die stryd teen apartheid het president Nelson Mandela hom in 1994 as Suid-Afrika se ambassadeur in Nederland aangestel.